Study on Lapping Position Control of Real Tooth Surface of Hypoid Gear - Yang Jianjun; Liu Linnan; Zhu Derong; Zhang Hua (Jixie chuandong)
In order to improve the lapping quality of hypoid gears,based on real tooth surface,an approach for lapping position control of hypoid gear is proposed. According to the measured results of real tooth surface of hypoid gears,the non-uniform rational B-spline（ NURBS） surface is employed to fit the measured points. The tooth contact analysis（ TCA） for the real measured tooth surface is applied to analyze the mathematic relationship between the adjusting parameters（ V/H/J） of lapping movement and the meshing position.The model of lapping point control over position and movement direction is established. Finally,a numerical control rolling test is carried out. The experimental results show that the whole tooth surface lapping of hypoid gears can be exactly realized.